Taste Masking Techniques of Unpleasant Drugs - Suza, Hiba M.; Hazim, Eman B. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Taste masking is one of the many processes that are used in the pharmaceutical industry. This is done with the intention masking or decreasing of a disagreeable taste or odor from the organic compounds which are usually used in the oral cavity and can be formulated by several types of techniques. Objective: To highlight the definition and importance of taste masking, the factors that affect taste masking, the many types of taste masking techniques that can be used, and the evaluation of taste masking in vitro and in vivo evaluations. Results: The masking of unpleasant taste or odor is important in the marketed product to improve patients’ compliance, especially for pediatric and geriatric patients, because it is necessary for the improvement of the therapeutic efficacy, and that’s can be obtained by several methods of taste-masking techniques; furthermore, these techniques may be simple, namely, like adding a sweetener or flavored agents, or by using other complicated methods like polymer coating, complexation, resin ionic exchange, external or internal ionic gelation, physical or chemical adsorption, granulation, microencapsulation, solid dispersion, effervescence, viscosity modification, nanosuspension, pro-drug and so on; it sometimes needs the combination of more than two methods to overcome very bad taste, and depends on the severity of the undesirable taste. Conclusion: The undesirable taste or odor can be masked by using different types of techniques depending on the intensity of the bad taste or odor, in addition to other factors that are related to the drug itself and the method of the dosage form that was chosen, and other factors. Taste masking was needed to improve patients’ compliance with the marketed products, and that is an important factor to ensure total completion of the drug course by patients.